The Real War - Nixon, Richard (Rawalpindi Army Education Press, 1980)
The former president examines the forces contending for power in today's world, assesses their goals, strategies and relative strengths and weaknesses, and weighs the implications of current trends.
Include Notes and Index.
Keywords: Diplomatic relations -- United States -- World politics